[RETRACTED] Quality Control Analysis of Bath Soap Products With Quality Control Circle (QCC) Method At Alliance Consumer Products Indonesia Uses to Minimize Failed Products - Zahra, Aulia; Aslami, Nuri; Atika, Atika (Quantitative Economics and Management Studies, 2024)
This article has been retracted following a formal complaint filed by PT. Alliance Consumer Products Indonesia (ACPI) regarding the accuracy of the data presented in this publication. The authors have informed the Editorial Board that the data used in the study does not accurately represent the actual conditions and quality control processes at PT. ACPI. Upon investigation based on the authors' acknowledgment, the Editorial Board confirmed that the data contained in the article is disputed by the company and cannot be verified as accurate. As the integrity and accuracy of research data is fundamental to the validity of scientific findings, the Editorial Board has decided to retract this article. The retraction was initiated based on the authors' notification following the complaint from PT. ACPI, and has been agreed upon by the Editorial Board in accordance with the Committee on Publication Ethics (COPE) Retraction Guidelines.     Abstract Every company, especially a manufacturing company, is required to maintain the quality of the products it makes, one of the ways to maintain or maintain the quality of the products is by carrying out quality control by using the Quality Control Circle (QCC) method. The purpose of this study was to determine the application and outcome of quality control on bath soap products at PT. Alliance Consumer Products Indonesia (ACPI). The research methodology used is a qualitative research method using primary data. The results of this study indicate that the quality control applied by the company has been going well. However, there are still some products that are defective. This is caused by several factors, namely machines, humans, and raw materials. To minimize defective products, the Quality Control division uses QCC (Quality Control Circle) and uses seven tools consisting of Check Sheets, Histograms, Scatter Diagrams, Flow Charts, Pareto Diagrams, Fishbone Diagrams and P Control Charts.